Evaluating local population dynamics of the American lobster, Homarus americanus, with trap‐based mark‐recapture methods and seabed mapping - Michael J. Dunnington; Richard A. Wahle; Michael C. Bell; Nathan R. Geraldi (New Zealand Journal of Marine and Freshwater Research, 2005)
Seabed mapping, spatially referenced trapping, and mark‐recapture methods have all been useful tools in ecological studies of lobsters and other benthic animals. Here we integrate the three methods to evaluate local population dynamics and movements of American lobsters, Homarus americanus, in coastal fishing grounds in Maine, United States. The study was conducted on five study areas of different size, and used two different sampling protocols. At one site (1 km 2 in area) we used a monthly mark‐recapture sampling interval over a 6‐month period, only tagging a subsample of the catch. At four smaller sites (0.3 km 2 ) we used a shorter‐term approach, sampling at 3–4‐day intervals for a 2‐week duration, tagging the entire catch. Tagging data were analysed with a modified Jolly‐Seber model adapted for continuous sampling to estimate population abundance, gains (immigration), and losses (emigration and mortality). Side‐scan sonar surveys of the seabed combined with diver‐based population surveys, stratified by substrate type, provided an independent comparison to mark‐recapture‐based estimates of abundance over the same areas. Spatial referencing of trap catch also allowed us to relate catch rates and lobster movements directly to seabed features. The longer‐term tagging data on the larger study area provided abundance estimates that were more consistent with the diver observations, and estimates of gains and losses statistically more robust, than those derived from the shorter‐term effort on the smaller sites. The flux of lobsters followed the well known seasonal movements on these fishing grounds, with gains and losses from the larger study area ranging over 1000 individuals per day, and an estimated mid‐summer peak density of >65 000 lobsters per km 2 (individuals >50 mm carapace length). This approach may lend itself to broader application with the American lobster.